F FORMULASI SABUN PADAT TRANSPARAN DENGAN PENAMBAHAN EKSTRAK BUNGA TELANG (Clitoria ternatea) - Nina Hartati; Melantina Oktriyanti; Erika Dwi Oktaviani (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2023)
Soap is one of the commodities of the beauty and medical sectors that have been utilized in daily life to purify the grime that adheres to the skin. Bath soap is categorized into two types, namely liquid and solid soap. Solid soap is comprised of 3 kinds, specifically cloudy, translucent, and transparant soap. Transparant solid soap is an innovation in beauty and body cleansing products that enhances the attractiveness of soap products with its translucence, softer lather, and shinier appearance compared to other types of solid soap. The primary ingredient used in this research for soap production is sodium hydroxide and coconut oil. Meanwhile, butterfly pea is used as an additional ingredient in this study to enhance the quality of soap products, both in terms of usability and appeal. In this study, the extraction of butterfly pea extract was conducted using the maceration method, and different variations of the extract were used, namely 4 ml, 6 ml, and 8 ml and variations of coconut oil used were 80 ml and 50 ml. Several analytical tests, including pH analysis, free alkali, free fatty acids, mineral oil, water content, and organoleptic tests, were performed to determine the feasibility of this transparent solid bath soap. Based on the analysis results of the solid bath soap, the best sample obtained was formulation A2, which used 80 ml of coconut oil with the addition of 6 ml of butterfly pea extract. The analysis results showed a pH value of 9, 0% free fatty acids, 0% free alkali, 13.6% water content, and no presence of mineral oil. Keywords : transparant solid soap, butterfly pea, sodium hydroxide, coconut oil